Molecular assessment of vitamin D receptor polymorphism as a valid predictor to the response of interferon/ribavirin‐based therapy in Egyptian patients with chronic hepatitis C. Issue 8 (August 2016) - Abdelsalam, Ahmed; Rashed, Laila; Salman, Tarek; Hammad, Lamiaa; Sabry, Dina
Abstract : Objective: The aim of this study was to find an association between serum concentration of vitamin D and vitamin D receptor ( VDR ) polymorphisms to achieve a sustained virological response (SVR). Methods: We conducted a case‐control study in which 250 participants were recruited and divided into three groups (100 chronic hepatitis C [CHC] patients who achieved SVR, 100 CHC patients who did not achieve SVR and 50 apparently healthy individuals as controls). Blood samples were collected to measure serum vitamin D concentration, and four VDR polymorphisms ( FokI, ApaI, TaqI, and BsmI ) were detected using polymerase chain reaction‐restriction fragment length polymorphism. Results: Non‐responders were found to have significantly low vitamin D concentration compared with responders and control groups. Concerning VDR polymorphisms, both FokI and TaqI polymorphisms were associated with successful treatment. Conclusion: Vitamin D concentration, FokI, and TaqI may be considered as the predictors for the response of CHC patients to a combination therapy of pegylated interferon and ribavirin.